Bursa atrophy at 28 days old caused by variant infectious bursal disease virus has a negative economic impact on broiler farms in Japan. Issue 1 (2nd January 2021) - Myint, Ohnmar; Suwanruengsri, Mathurot; Araki, Kenji; Izzati, Uda Zahli; Pornthummawat, Apisit; Nueangphuet, Phawut; Fuke, Naoyuki; Hirai, Takuya; Jackwood, Daral J.; Yamaguchi, Ryoji
ABSTRACT: Infectious bursal disease (IBD), caused by IBD virus (IBDV), is highly contagious, immunosuppressive and causes a negative economic impact on poultry industry. IBDV-vaccinated broiler farms at south Kyushu, Japan had a bursa-to-bodyweight ratio (BB ratio) reduction at 28 days (d) old, followed by high mortality 30 d later. We analysed the influence of the IBDV on atrophy of the bursa of fabricius (BF) and the subsequent mortality after 30 d. Ten broilers were sampled at each timepoint from the farm with high mortality at 21, 25, 28 and 35 d. A second flock from the same farm was sampled at 14, 21, 25, 28, 35 and 42 d. IBDV was detected in BF samples at 25, 28 and 35 d and at 21, 25, 28 and 35 d in the first and second flocks, respectively, using immunohistochemical staining and RT-PCR. IBDV isolates from both flocks were closely related to the China KM523643 strain. Histopathology and TUNEL assay indicated apoptosis, severe lymphoid depletion, vacuoles within follicles, lymphoid follicle atrophy and fibrosis in the BF. We observed 75% of the polyserositis and 10% of the airsacculitis at 30 D in dead broilers. The antigenic variant IBDV infection was appeared to be the main influencing factor on BF atrophy and BB ratio reduction in the broilers. High mortality in the broilers after 30 d could be due to secondary infection. The disease caused by IBDV had a negative economic impact in the farm. RESEARCH HIGHLIGHTS New variant IBDV caused bursa atrophy and reduced BB ratio in 28-day-old broilers. After vIBDV had infected broilers, at 21 days old they became immunosuppressed. High mortality at 30 days old in broilers was due to secondary infection. New vIBDV has a negative economic impact on broiler farms in Japan.